The Influence of Organizational Commitment, Work Environment, and Organizational Citizenship Behavior on Public Service Motivation among Sub-district Employees - Rahmah Fajria; Syamsir Syamsir (Journal of Education on Social Science (JESS), 2025)
This study aims to explore the extent to which participation in the organization, work environment conditions, and organizational citizenship behavior (OCB) affect the morale of subdistrict employees in Lima Puluh Kota Regency. The background of this study is the low morale that has an impact on the quality of public services, especially in several subdistrict areas. The population in this study included all subdistrict employees in Lima Puluh Kota District, with 95 respondents selected randomly and proportionally. Data were collected through the distribution of questionnaires and analyzed using multiple linear regression and path analysis techniques. The results revealed that commitment to the organization, work environment, and OCB together have a significant effect on enthusiasm in providing public services. Among the three, OCB showed the most dominant influence on public service motivation. Based on these results, this study recommends strengthening organizational culture, providing institutional support, and encouraging positive behavior to increase the enthusiasm of the apparatus in public services.